(3eGjSJMH heG jLJfH aj TghQ GdSfIs - (3Mfjf Hf ESMGb , CHh RjO Mfjf Hf ESMGb GdYHGOj,J (B260 (3g` s
(3ChdgG (B:s
(3bGd Mfjf Hf ESMGb (B: (3PcQ adWjfS GdMcje (B( (3CadGWhf(B) (3Cf cfhf GdChd efgG OLfHQ hcGfhf GdBNQ jfjQ, hTHGW aHQGjQ, JYGgO ajgf HGdSaha hHGdCTLGQ GdMGQI hGdVeGOGJ GddjfI s
(3BNQgG (B:s
(3hCMeO Gddg GdPi LYd dc GdSHb ai ESJNQGLg , hTQa geJc HGdJWdY Ydjg , hCdgec Edi ebOGQ faYg, hLdjd NWQg , hgh MSHc ajeG CedjJg hfYe Gdhcjd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B287 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B87s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B215 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs